2010
DOI: 10.1007/s10653-010-9367-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing nitrate contamination and its potential health risk to Kinmen residents

Abstract: Kinmen is located in the southwest of Mainland China. Groundwater supplies 50% of the domestic water use on the island. Residents of Kinmen drink groundwater over the long term because surface water resources are limited. Nitrate-N pollution is found and distributed primarily in the western part of groundwater aquifer whereas saline groundwater is distributed to the northeastern Kinmen. This work applied the DRASTIC model to construct the vulnerability map of Kinmen groundwater. MT3D was then used to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Furthermore, it can also be observed that, the risky areas (HQ nitrate N 1) for children are higher than that of adults, reaffirming the fact that children are more vulnerable than adults. Non-carcinogenic risk of NO 3 − in drinking water is becoming a major concern to many countries where majority of the population, especially in rural areas, depend on groundwater (Nadia et al, 2015;Liu et al, 2011;Chen et al, 2016). In view of the rising trend in nitrate concentration in the drinking water and the vulnerability of the study area, the relevant stakeholders such as government, district assemblies, water resources managers and the communities must lay emphasis on the protection of public sources of drinking water so as to protect public health.…”
Section: Health Risk Assessment Associated With Nitrate Contaminationmentioning
confidence: 99%
“…Furthermore, it can also be observed that, the risky areas (HQ nitrate N 1) for children are higher than that of adults, reaffirming the fact that children are more vulnerable than adults. Non-carcinogenic risk of NO 3 − in drinking water is becoming a major concern to many countries where majority of the population, especially in rural areas, depend on groundwater (Nadia et al, 2015;Liu et al, 2011;Chen et al, 2016). In view of the rising trend in nitrate concentration in the drinking water and the vulnerability of the study area, the relevant stakeholders such as government, district assemblies, water resources managers and the communities must lay emphasis on the protection of public sources of drinking water so as to protect public health.…”
Section: Health Risk Assessment Associated With Nitrate Contaminationmentioning
confidence: 99%
“…Nitrate pollution of water is a worldwide problem associated with the extensive use of nitrogen fertilizers and manure in agricultural fields (Liu et al 2011;Ahmad et al 2014b). Elevated NO 3 levels in drinking water are toxic to humans, causing methemoglobinemia in infants and cancer of the digestive tract (Keshavarzi et al 2012;Camargo et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrate in drinking water may pose a health risk when the levels exceed the MCL of 10 mg L −1 (Coss et al, 2004;Liu et al, 2011). Agriculture uses large amounts of fertilizer and manure compost on farming lands, causing the significant nitrate pollution in groundwater.…”
Section: Discussionmentioning
confidence: 99%
“…For example, infants below 6 months could become seriously ill and may cause fatality due to nitrate exposure. The symptom of nitrate toxic is shortness of breath and blue-baby syndrome (Liu et al, 2011). Besides, long term exposure to low levels of nitrate presents a noncarcinogenic risk to human (Majumdar and Gupta, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation